Time-efficient BER estimation approach using jitter characteristics for HBC channel - Li, Jia Wen; Mak, Peng Un; Pun, Sio Hang; Chen, Xi Mei; Che, U Kin; Lam, Chan Tong; Gao, Yue Ming; Vai, Mang I; Du, Min (IET science, measurement & technology, 2018)
As a physical layer of body area network, human body communication (HBC) has become a prospective candidate with advantages of less interference and intrinsic transmission for implanted devices. Currently, its bit error rate (BER) performance has not been thoroughly reported with high confidence because the traditional BER testing method in commonly used wireless radio and optical system communication, if directly applying in HB channel, is both time-consuming and problematic due to significant physiological limitations. In this study, a time-efficient approach using jitter characteristics is proposed to tackle this problem. To practically measure the BER in HBC channel, experiments based on human arms are carried out with 600 records of jitter data (5 subjects, 3 modulation schemes, 4 separation distances, and 10 transmit power levels). By using both normal probability plot and Kolmogorov–Smirnov test, the authors found that the HBC experimental jitter data mainly followed normal distribution. Additionally, the comparison between estimated BERs using their approach match well with those via the theoretical prediction based on additive white Gaussian noise channel. Finally, the proposed approach can be an effective measurement method not only for the BER of body channel, but also applicable in other similar low rate systems.